Determinants of Muslim Family's Staying Interest at a Sharia Hotel in Surakarta - Kurniawan, Fendy; Safitri, Lia Ardiana (Media Wisata, 2025)
The concept of halal tourism is a concept that integrates sharia values into tourism activities by providing facilities and services that comply with sharia provisions. halal purposes. Meanwhile, the aim of this research is to determine the influence of products, services and management on Muslim families' interest in staying overnight at sharia hotels in Surakarta. The population in this study were hotel customers/consumers who were staying at sharia hotels in Surakarta, while the sample was 36 hotel customers/consumers who were staying at sharia hotels in Surakarta. The results of this research are that the product variable (X1) has a significant effect on interest in staying overnight. The service variable (X2) has a significant effect on interest in staying and the management variable (X3) has a significant effect on interest in staying.